Restless guests: tourists in literary works. A changing life strategy and practice - Razbojnikova-Frateva, Maja (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
In his sketch “The Blind Man”, Elias Canetti depicts a person with a camera in his hand who travels the world with his eyes closed and only wants to look at it in photos. The tourist is easily recognized in this figure’s basic attitude. In view of the constant characteristics of tourist travel, as it has emerged as a life strategy and practice from the 19th century to the present day, the article examines the question of whether tourism and tourists (as a characteristic social figure) have really remained untouched by the accelerating social and technological development, as several literary texts since the 19th century suggest. The subject-world relationship is identified as a suitable area in which changes can be observed. In Canetti’s sketch, too, the special relationship to the world, hidden behind well-known tourist practices, is surprising. Hartmut Rosa’s sociology of world relations with its central concept of resonance provides the theoretical framework against which two novels – Christoph Ransmayr’s “The Terrors of Ice and Darkness” and Ilija Trojanow’s “Ice Jam” are analyzed. The protagonists’ search for resonance may lead to catastrophe and death, but it points to the need for a resonant relationship with the world as the basis for a good and successful life. Heidegger’s text of the same name is used as a positive counter-proposal in which “stays” appear possible as a resonance experience in and with the world.
Keywords: tourist; tourism; social figure; world relationship; resonance